Modeling the total dust production of Enceladus from stochastic charge equilibrium and simulations. (15th December 2015) - Meier, Patrick; Motschmann, Uwe; Schmidt, Jürgen; Spahn, Frank; Hill, Thomas W.; Dong, Yaxue; Jones, Geraint H.; Kriegel, Hendrik
Abstract: Negatively and positively charged nano-sized ice grains were detected in the Enceladus plume by the Cassini Plasma Spectrometer (CAPS). However, no data for uncharged grains, and thus for the total amount of dust, are available. In this paper we estimate this population of uncharged grains based on a model of stochastic charging in thermodynamic equilibrium and on the assumption of quasi-neutrality in the plasma-dust system. This estimation is improved upon by combining simulations of the dust component of the plume and simulations for the plasma environment into one self-consistent model. Calibration of this model with CAPS data provides a total dust production rate of about 12 kg s −1, including larger dust grains up to a few microns in size. We find that the fraction of charged grains dominates over that of the uncharged grains. Moreover, our model reproduces densities of both negatively and positively charged nanograins measured by Cassini CAPS. In Enceladus׳ plume ion densities up to 10 4 cm − 3 are required by the self-consistent model, resulting in an electron depletion of about 50% in the plasma, because electrons are attached to the negatively charged nanograins. These ion densities correspond to effective ionization rates of about 10 − 7 s − 1, which are about two orders of magnitude higher than expected. Abstract : Highlights: We derive an equilibrium charging model for nano-sized dust in the Enceladus plume. Based on our model we estimate dust production rates at Enceladus that are consistent with CAPS data for negatively and positively charged grains. We estimate the fraction of uncharged dust grains in the Enceladus plume.